Physical performance measures for predicting outcome in cancer patients: a systematic review. (1st December 2016) - Verweij, Norbert M.; Schiphorst, Anandi H. W.; Pronk, Apollo; van den Bos, Frederiek; Hamaker, Marije E.
Abstract: Background: Decision making regarding cancer treatment is challenging and there is a need for clinical parameters that can guide these decisions. As physical performance appears to be a reflection of health status, the aim of this systematic review is to assess whether physical performance tests (PPTs) are predictive of the clinical outcome and treatment tolerance in cancer patients. Methods: A literature search was conducted on 2 April 2015 in the electronic databases Medline and Embase to identify studies focusing on the association between objectively measured PPTs and outcome. No limitations in language or publication dates were applied. Results: The search retrieved 9680 articles, 16 publications were included involving 4187 patients with various cancer types and different treatments. Reported median or mean age varied from 58 to 78 years. Nine studies used the Timed Up & Go (TUG) test, five the Short Physical Performance Battery (SPPB) and five studies focused on gait speed. Poorer TUG, SPPB and gait speed outcome were associated with decreased survival. TUG, SPPB and gait speed were also associated with treatment-related complications. Furthermore, two studies reported an association between poorer TUG and SPPB outcome with higher rates of functional decline. Conclusion: PPTs appear to show a significant correlation with survival and these tests could be used as a prognostic tool, particular for older adult patients. A less explicit correlation for treatment-related complications and functional decline was also found. To optimize decision making, future research should focus on developing and validating individualized treatment algorithms that incorporate PPTs in addition to cancer- and treatment-related variables.